(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Kravtsova I. A. The formation and development of elocution skills of primary school pupils in terms of new state standard. The article deals with the problem of the formation and the development of elocution skills of primary school pupils accordiny to the requirements of the new state standard. The author studies the effective methods and techniques of teaching elocution for school pupils and saddest the system of tasks, aimed at the formation of lyrics analysis skills at readily lessons.